2010
DOI: 10.1177/0743558410366596
|View full text |Cite
|
Sign up to set email alerts
|

“We Were Best Friends, But . . . ”: Two Studies of Antipathetic Relationships Emerging From Broken Friendships

Abstract: Antipathetic relationships and friendships are common during adolescence. One type of antipathetic relationship that has received no empirical att en tion is one that emerges from a broken friendship. Two studies, a reana lysis of N. A. Card's previously published data (Study 1) and newly collected data (Study 2), investigated this topic through mixedmethods analysis of emerging adults' retrospective reports of relationships during high school. Qualitative analyses revealed jealousy, incompatibility, intimacyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…Although antipathies are inherently relational in nature, in only a few studies have they been treated from a social network perspective in which antipathies were examined together with positive peer relationships, revealing an interplay between the two types of relationships (Berger and Dijkstra, 2013;Casper and Card, 2010;Huitsing et al, , 2014. Casper and Card (2010) showed how friendship relationships might turn into antipathetic relationships; four other studies examined the specific network configurations underlying negative and positive peer relationships among students in primary school.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Although antipathies are inherently relational in nature, in only a few studies have they been treated from a social network perspective in which antipathies were examined together with positive peer relationships, revealing an interplay between the two types of relationships (Berger and Dijkstra, 2013;Casper and Card, 2010;Huitsing et al, , 2014. Casper and Card (2010) showed how friendship relationships might turn into antipathetic relationships; four other studies examined the specific network configurations underlying negative and positive peer relationships among students in primary school.…”
mentioning
confidence: 98%
“…Casper and Card (2010) showed how friendship relationships might turn into antipathetic relationships; four other studies examined the specific network configurations underlying negative and positive peer relationships among students in primary school. Using advanced methods (i.e., social network analyses), Huitsing and colleagues showed both cross-sectionally and longitudinally (Huitsing et al, 2014) that victims with the same bullies and bullies with the same http://dx.doi.org/10.1016/j.socnet.2015.05.003 0378-8733/© 2015 Elsevier B.V. All rights reserved.…”
mentioning
confidence: 98%
“…Jealousy has been identified previously as a predictor of conflict in both female pre-adolescents (Crick & Grotpeter, 1995), and adolescents (Casper & Card, 2010). Kamphoff, Gill, and Huddleston (2005) found that jealousy on sport teams not only exists, but also can have a negative impact on team cohesion.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Similarly, coaches" perceptions of the Furthermore, longitudinal research is needed to determine the potential long-term outcomes of peer conflict in sport when performance is impacted for the entire group (e.g., through game exclusionary tactics), as well as how peer relationships may change over the course of a season, rather than at only one specific time as previous research has suggested that adolescent relationships are often characterized by negative components such as conflict (Smith & Weiss, 2002), and broken friendships (Casper & Card, 2010).…”
Section: Implications and Conclusionmentioning
confidence: 98%
See 1 more Smart Citation